2020
DOI: 10.1101/2020.08.20.20174169
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Associations of comorbidities and medications with COVID-19 outcome: A retrospective analysis of real-world evidence data

Abstract: Background: Hundreds of thousands of deaths have already been recorded for patients with the severe acute respiratory syndrome coronavirus (SARS-CoV-2; aka COVID-19). Understanding whether there is a relationship between comorbidities and COVID-19 positivity will not only impact clinical decisions, it will also allow an understanding of how better to define the long-term complications in the groups at risk. In turn informing national policy on who may benefit from more stringent social distancing and shielding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 12 publications
1
27
0
1
Order By: Relevance
“…As reported in a retrospective cohort of hospitalized patients in the UK, long-term antidiabetic medications reduced COVID-19 mortality in diabetic patients(25), which was a very encouraging finding, especially as diabetic patients are particularly susceptible to cumulative organ injury by SARS-CoV-2 because of already compromised pulmonary, cardiac and renal functions. Therefore, furthering our understanding of antidiabetic medications can yield a practical and effective approach in dramatically improving outcomes in this vulnerable population disproportionately affected by COVID-19.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…As reported in a retrospective cohort of hospitalized patients in the UK, long-term antidiabetic medications reduced COVID-19 mortality in diabetic patients(25), which was a very encouraging finding, especially as diabetic patients are particularly susceptible to cumulative organ injury by SARS-CoV-2 because of already compromised pulmonary, cardiac and renal functions. Therefore, furthering our understanding of antidiabetic medications can yield a practical and effective approach in dramatically improving outcomes in this vulnerable population disproportionately affected by COVID-19.…”
Section: Discussionmentioning
confidence: 53%
“…16 studies were included in qualitative synthesis. Among these, 12 studies related to metformin(15, 16, 25-35), 6 studies related to DPP-4i(27, 28, 33, 35-38), 3 studies related to sulfonylurea or glinides(27, 28, 33, 35), 2 studies related to SGLT-2i(33, 35) and 1 study related to GLP-1RA(27, 28). Some of these studies included multiple outcomes to different medications.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, two smaller retrospective study by Abu-Jamous et al. [ 24 ] and Crouse et al. [ 25 ] involving 411 and 239 patients with diabetes also showed an 81% (OR: 0.19 (0.05–0.70), p = not reported) and 67% (OR 0.33; 95% CI 0.13–0.84; p = 0.02) relative risk reduction of death, respectively, in those who were metformin users compared to the non-users.…”
Section: Non-insulin Anti-diabetic Drugs In Covid-19mentioning
confidence: 86%
“…Meanwhile, several small to large retrospective studies and one large prospective study have reported the outcomes with metformin in patients of T2DM with COVID-19 [ [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] ]. While some studies [ [17] , [18] , [19] , [20] , [21] ] found neither any harm nor any benefit in metformin users when compared to non-users both in severity and mortality outcomes, majority [ [23] , [24] , [25] , [26] , [27] , [28] , [29] ] reported a significant reduction in mortality. Interestingly, one study reported even an increase in severity in metformin users [ 22 ].…”
Section: Non-insulin Anti-diabetic Drugs In Covid-19mentioning
confidence: 99%